We have the expression: (x-5)^2 + 1 = 3x - 4

(x-5)^2 + 1 = 3x - 4

open the brackets

x^2 + 25 - 10x + 1 = 3x - 4

=> x^2 - 10x - 3x + 26 + 4 = 0

=> x^2 - 13x + 30 = 0

The expression is a quadratic equation.

If we have to find the solutions

x^2 - 13x + 30 = 0

=> x^2 - 10x - 3x + 30 = 0

=> x(x - 10) - 3( x - 10) = 0

=> (x - 3)(x - 10) = 0

=> x = 3 and x = 10

**The given expression is a quadratic equation.**

## See eNotes Ad-Free

Start your **48-hour free trial** to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Already a member? Log in here.